Advanced Atrioventricular Block in a Young Patient: Pacemaker Implantation Is No Longer the Only Choice - May, Bruna Miers; Bartholomay, Eduardo; Kochi, Adriano Nunes; Andrade, Karina; Nicola, Thaís Coutinho; Reichert, Giulia Bonatto (Pacing and clinical electrophysiology, 2025)
ABSTRACT A 40‐year‐old woman with symptomatic advanced atrioventricular (AV) block underwent cardioneuroablation (CNA) for the treatment of functional bradyarrhythmia, following the exclusion of reversible causes and intrinsic disease of the conduction system. Selective ablation of ganglia related to the AV node, performed exclusively in the left atrium, restored AV conduction, which has remained unchanged with 2 years of follow‐up. CNA is a viable and effective option with low risk for the treatment of functional bradyarrhythmias, regardless of their severity.